PENGEMBANGAN MEDIA PEMBELAJARAN KARTIK (KARTU TEMATIK) TEMA 8 KESELAMATAN DI RUMAH DAN DI PERJALANAN BAGI SISWA SEKOLAH DASAR KELAS II - Amaliyah Ulfah (Profesi Pendidikan Dasar, 2019)
Abstract The lack of media in thematic learning underlies this study. This study aims at developing KARTIK (Thematic Card), and specifically describes, (1) steps of KARTIK media development, (2) feasibility of KARTIK according to experts, (3) students' responses to the KARTIK media. Drawing upon the notions developed by this Research and Development consisted of seven stages, namely collecting information, planning, developing preliminary product, preliminary field testing, main product revision, main field testing, and revision. The subjects in this study were 10 graders of Grojogan Public Elementary School in limited trial and 30 students in the main trial. Questionnaires were used for data collection, and the data was analyzed using quantitative descriptive. The KARTIK media was developed through seven steps, namely determining the theme, designing card, designing content, designing user manual, designing card box, expert validation, and product trial. The results showed that the KARTIK media was appropriate for use for grade II primary school students. Media experts score 86 (very good), material experts score 42 (good), and learning experts score 40 (good). The Students responses were 96.92% (very good) and 98.2% in the main group trials. The KARTIK media was declared appropriate for use.